2018
DOI: 10.1139/cjb-2018-0084
|View full text |Cite
|
Sign up to set email alerts
|

Communities of arbuscular mycorrhizal fungi in maize (Zea mays L.) crops along an edaphoclimatic gradient in Northeast Brazil

Abstract: The objective of this study was to determine the species richness, diversity, and communities of arbuscular mycorrhizal fungi (AMF), based on the morphology of their spores, in maize plantations along an edaphoclimatic gradient going from a humid zone (original area of Atlantic rainforest), to a transition zone and a drier zone (original area of Caatinga), to increase the understanding of the ecology of AMF in tropical agroecosystems. We extracted glomerospores from soil samples from maize plantations in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
3
1
Order By: Relevance
“…A work carried out in Cameroon, comparing natural and anthropic ecosystems, reported AMF spore diversity values (Shannon index) as low as 0.39 for agricultural sites, with forests being richer (0.49) (Snoeck et al 2010 ). These figures are especially low considering reports of AMF spore diversity (Shannon) of 1.4 and 2.27 in alfalfa and sorghum crops in Sudan (Abdelhalim et al 2014 ), 1.96 in maize in Brazil (de Mello et al 2018 ), 2.65 in cassava (Sarr et al 2019 ), and between 1.65 and 2.75 in this study using amplicon sequencing.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…A work carried out in Cameroon, comparing natural and anthropic ecosystems, reported AMF spore diversity values (Shannon index) as low as 0.39 for agricultural sites, with forests being richer (0.49) (Snoeck et al 2010 ). These figures are especially low considering reports of AMF spore diversity (Shannon) of 1.4 and 2.27 in alfalfa and sorghum crops in Sudan (Abdelhalim et al 2014 ), 1.96 in maize in Brazil (de Mello et al 2018 ), 2.65 in cassava (Sarr et al 2019 ), and between 1.65 and 2.75 in this study using amplicon sequencing.…”
Section: Discussioncontrasting
confidence: 54%
“…Recent efforts have been made to bridge this gap. However, most of these studies have focused on extraction of AMF spores from the soil and subsequent morphological identification (Abdelhalim et al 2014;de Mello et al 2018;Sousa et al 2018;Marinho et al 2019;Solís-Rodríguez et al 2020) rather than using DNA sequences for identification. Large degrees of variation in spore morphology have been reported even within an AMF species (Walker and Vestberg 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The production of spores is part of the AMF life cycle and is highly dependent on environmental conditions, their physiological status and life strategy (de Mello et al, 2018; Smith & Read, 1997). We found that MAP was the best predictor of AMF spore abundance worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…In Caatinga plants, Mimosa tenui ora, the most common AMF species in the rhizosphere was Ambispora apendicula, while in Commiphora leptophloeos, the most common AMF species in the rhizosphere were Acaulospora scrobiculata, Gigaspora margarita and Racocetra fulgida (Teixeira-Rios et al, 2018). In an area of Caatinga in Serra Talhada, Acaulospora excavata and Acaulospora denticulata dominated (Mello et al, 2018). While in native and regenerating Caatinga, in addition to pasture, Acaulospora scrobiculata, Glomus macrocarpum and Glomus tortuosum were the AMF species found in all areas (Santos et al, 2018).…”
Section: Resultsmentioning
confidence: 99%